2003
DOI: 10.1002/ptr.1377
|View full text |Cite
|
Sign up to set email alerts
|

Activity against multidrug‐resistant Mycobacterium tuberculosis in Mexican plants used to treat respiratory diseases

Abstract: The increase of multidrug-resistant Mycobacterium tuberculosis (MDR-TB) demands the search for alternative antimycobacterial drugs. The aim of this study was to evaluate plants used in Mexican traditional medicine to treat respiratory diseases for activity against MDR-TB. A group of 22 plants was screened for activity against Mycobacterium tuberculosis H37Rv and Mycobacterium avium at concentrations from 50 to 200 microg/mL. The antimycobacterial effect was determined by a microcolorimetric assay with Alamar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 21 publications
1
97
0
1
Order By: Relevance
“…The activities of all test samples against M. tuberculosis were evaluated using the Microplate Alamar Blue Assay (MABA) according to Collins and Franzblau (1997) as modified by Jimenez-Arellanes et al (2003). M. tuberculosis was cultured at 37°C in Middlebrook 7H9 broth.…”
Section: Antituberculosis Assay Using M Tuberculosis: Maba Susceptibmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities of all test samples against M. tuberculosis were evaluated using the Microplate Alamar Blue Assay (MABA) according to Collins and Franzblau (1997) as modified by Jimenez-Arellanes et al (2003). M. tuberculosis was cultured at 37°C in Middlebrook 7H9 broth.…”
Section: Antituberculosis Assay Using M Tuberculosis: Maba Susceptibmentioning
confidence: 99%
“…Samples with detected MIC values following MABA (Collins & Franzblau, 1997;Jimenez-Arellanes et al, 2003) were assayed for their mycobactericidal effect as follows. The mycobacterial suspensions showing no growth (5 μL) were transferred from the former to a new microplate that contained 195 μL of fresh culture medium.…”
Section: Determination Of Mycobactericidal Effect (Mbc)mentioning
confidence: 99%
“…Literature search (Van Puyvelde et al, 1994;Boily;Van Puyvelde, 1986) showed that a crude ethanolic extract of Lantana trifolia collected in Rwanda, and prepared in the same way as ours had been previously assayed for antimycobacterial activity -M. smegmatis (Boily;Van Puyvelde, 1986) and clinical strains of M. tuberculosis (Van Puyvelde et al, 1994), and similarly, no positive activity was found, corroborating with our results. However, the report on the antimycobacterial activity of another species from the genus Lantana -L. hispida (Jimenez-Arellanes et al 2003), prompted us to investigate this activity on the Lantana trifolia fractions. The active hexane and dichloromethane fractions from the leaves of Lantana trifolia, Lippia lacunosa and Lippia rotundifolia are now being submitted to bioassay-guided fractionation to locate the active(s) substance(s).…”
Section: Resultsmentioning
confidence: 99%
“…The activity of all phytochemicals against the aforementioned M. tuberculosis strains was tested using the microplate Alamar Blue assay described previously [14][15] . Sterile distilled water (200 ml) was poured into outer perimeter wells of the microplate.…”
Section: Antimycobacterial Activitymentioning
confidence: 99%